A new species of Acanthocaudus Smith (Braconidae: Aphidiinae), with a key to species and new host and distribution records for aphidiines associated with Silphium perfoliatum L. (Asterales: Asteraceae) - Kula, Robert R.; Johnson, Paul J.; Heidel-Baker, Thelma T.; Boe, Arvid (Zootaxa, 2017)
A new species, Acanthocaudus bicolor Kula (Braconidae: Aphidiinae), from the Nearctic Region is described and differentiated from all other species of Acanthocaudus Smith. Acanthocaudus schlingeri Muesebeck, 1958 is synonymized with Acanthocaudus tissoti (Smith, 1944). A key to the species of Acanthocaudus is provided. The following aphidiines are reported as parasitoids of aphids on Silphium perfoliatum L. (cup plant) for the first time: Aphidius (Aphidius) ohioensis ex Uroleucon (Uroleucon) cf. rudbeckiae (Fitch), Aphidius (Aphidius) polygonaphis (Fitch) ex Uroleucon sp., Praon pequodorum Viereck ex undetermined aphids, and Praon simulans (Provancher) ex undetermined aphids. Aphidius (A.) ohioensis and P. simulans are reported from Indiana and South Dakota for the first time. Acanthocaudus tissoti and P. pequodorum are reported from Indiana for the first time.